2018
DOI: 10.1002/hep.29627
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐21 and Dicer are dispensable for hepatic stellate cell activation and the development of liver fibrosis

Abstract: Genetic and pharmacologic manipulation of miR-21 does not inhibit the development of liver fibrosis and liver cancer. Moreover, suppression of microRNA synthesis does not significantly affect HSC phenotype and activation. (Hepatology 2018;67:2414-2429).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 52 publications
(188 reference statements)
1
54
0
1
Order By: Relevance
“…In contrast to these studies (Table ), in the current issue of H epatology , Caviglia et al report that miR‐21 is not crucial for the activation of hepatic stellate cells (HSCs) or the development of liver fibrosis. To reach this conclusion, the investigators performed rigorous examinations with genetic and pharmacologic manipulation of miR‐21 in multiple models of liver fibrosis.…”
Section: In Vivo Preclinical Studies Showing Mir‐21 Profibrotic Effectsmentioning
confidence: 75%
“…In contrast to these studies (Table ), in the current issue of H epatology , Caviglia et al report that miR‐21 is not crucial for the activation of hepatic stellate cells (HSCs) or the development of liver fibrosis. To reach this conclusion, the investigators performed rigorous examinations with genetic and pharmacologic manipulation of miR‐21 in multiple models of liver fibrosis.…”
Section: In Vivo Preclinical Studies Showing Mir‐21 Profibrotic Effectsmentioning
confidence: 75%
“…Hepatic stellate cell (HSC) activation is regarded as the important event in the progression of liver fibrosis . Recently, it has been reported that many noncoding RNAs have been linked to HSC activation . However, the function and underlying mechanism of noncoding RNAs in liver fibrosis is far from being fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Angiotensin II and HSCs are the main responsible parameters involved in the fibrosis of the liver [66,67]. Moreover, the roles played by microRNA-21 in the induction of liver fibrosis have been documented previously [68,69]. For instance, it has been reported that transforming growth factor beta (TGF-β) is an important molecule, which participates in the induction of inflammation and also fibrosis in the liver via interaction with receptor-regulated SMAD (mothers against decapentaplegic drosophila homolog) proteins (R-SMADs) [4,70].…”
Section: Inflammasomes; the Crucial Inducers Of Chronic Inflammation mentioning
confidence: 85%
“…It has been documented that mitophagy is a biological process to remove the dysfunctional mitochondria, which is a main cause of cancers [84]. FUN14 domain containing 1 (FUNDC1), a well-characterized mitophagy receptor, mediates mitophagy and consequently suppresses HCC induction through inhibition of inflammasome activation, including caspase-1 and IL-1β [68]. Additionally, it has been demonstrated that increased background non-tumorous hepatocyte levels of NLRP3, NLRC4, and caspase-1 have significant correlations with poor HCC prognosis [85].…”
Section: Inflammasomes; the Crucial Inducers Of Chronic Inflammation mentioning
confidence: 99%